2012
DOI: 10.1137/100807983
|View full text |Cite
|
Sign up to set email alerts
|

Almost Local Metrics on Shape Space of Hypersurfaces inn-Space

Abstract: Abstract. This paper extends parts of the results from [P.W. Michor and D. Mumford, Appl. Comput. Harmon. Anal., 23 (2007), pp. 74-113] for plane curves to the case of hypersurfaces in R n . Let M be a compact connected oriented n − 1 dimensional manifold without boundary like the sphere or the torus. Then shape space is either the manifold of submanifolds of R n of type M , or the orbifold of immersions from M to R n modulo the group of diffeomorphisms of M . We investigate almost local Riemannian metrics o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 14 publications
(21 reference statements)
1
91
0
Order By: Relevance
“…Then geodesics of very long translations will go via a strong shrinking part and growing part, and almost all of the translation will be done with the shrunken version of the shape. This behavior, which also occurs for the class of conformal metrics, is described in [12]. 6 Sobolev type metrics on shape space Sobolev-type inner metrics on the space Imm(M, R d ) of immersions are metrics of the form…”
Section: Examplesmentioning
confidence: 84%
See 4 more Smart Citations
“…Then geodesics of very long translations will go via a strong shrinking part and growing part, and almost all of the translation will be done with the shrunken version of the shape. This behavior, which also occurs for the class of conformal metrics, is described in [12]. 6 Sobolev type metrics on shape space Sobolev-type inner metrics on the space Imm(M, R d ) of immersions are metrics of the form…”
Section: Examplesmentioning
confidence: 84%
“…A reason for this might be that the distance between the two boundary shapes is not sufficiently large. In the article [12] it has been shown that this behavior carries over to the case of higher-dimensional surfaces, c.f. Fig.…”
Section: Examplesmentioning
confidence: 91%
See 3 more Smart Citations